1984
DOI: 10.1515/znc-1984-0608
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Defense of Lupins. Mollusc-Repellent Properties of Quinolizidine Alkaloids

Abstract: Quinolizidine Alkaloids, M ollusc Repellency, C oevolution, Plant-H erbivore Interaction, Snails, Chemical Defense Polyphagous molluscs such as H elix pom atia and Arion rufus generally do not feed on plants containing alkaloids. O f 19 species tested 10 species were totally avoided, the other 9 species were less attacked than Lactuca sativa, which was readily taken. Plants containing quinolizidine alkaloids were studied in detail. Those species with the a-pyridone alkaloids cytisine and N-methylcytisine were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
2

Year Published

1985
1985
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 18 publications
2
36
0
2
Order By: Relevance
“…Furthermore, lupins are characterized by a rich secondary metabolism and the production of alkaloids, phytoalexins and flavonoids [7,8]. Some of these biologically active substances have potential applications in medicine and in pest control [9,10]. Despite their obvious advantages as a crop, lupins are still of minor importance in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, lupins are characterized by a rich secondary metabolism and the production of alkaloids, phytoalexins and flavonoids [7,8]. Some of these biologically active substances have potential applications in medicine and in pest control [9,10]. Despite their obvious advantages as a crop, lupins are still of minor importance in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that lupin extract exhibits repellent activity against Colorado beetle (Wyrostkiewicz et al 1996) as well as bacteriostatic (Tyski et al 1988, Wink 1994, and fungistatic activity (Wink 1994). Cwojdziński et al (1997) believe that, the extract has positive effect on yield when optimal growing conditions during plant cultivation are ensured i.e.…”
Section: Results and Disscussionmentioning
confidence: 99%
“…It seems that explanation of action mode of lupin extract should be looked for in its chemical composition, in particular relatively high amount of alkaloids (95.8 g⋅kg -1 ). It may be supposed that so-called minor alkaloids, present also in lupin extract, play very important role of stimulators of photosynthesis process (Wink 1994). According to this author, in plants sprayed with solution of alkaloids photosynthesis may be intensified supplying plants with additional carbohydrates, which may be used as an energy source for nitrates reduction.…”
Section: Results and Disscussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinolizidine alkaloids are plant defensive compounds against herbivores (Wink 1984, 1992a, Wink and Römer 1986. There are high concentrations of these alkaloids in seeds of lupines (1-4% of dried weight) (Wink 1992a, Carey andWink 1994).…”
Section: Introductionmentioning
confidence: 99%